PENGARUH PEMBELAJARAN PROYEK TERHADAP KEMAMPUAN MENULIS KREATIF PUISI SATIRE SISWA KELAS X MAN PURWOREJO - Adelya Indradini, Alda; Sholeh, Khabib; Daru Santoso, Suryo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study addresses the challenges in creative writing instruction, specifically the low ability of students to process vocabulary and language structures, a lack of critical social awareness, and the prevalence of conventional teacher-centered methods that limit active student engagement. The objective of this research is to examine the differences in creative satire poetry writing abilities between students taught using the Project-Based Learning (PjBL) model and those taught using conventional methods, as well as to measure the overall effectiveness of the PjBL model. Utilizing a quantitative approach with a Posttest-Only Control Group Design, this study involved 66 tenth-grade students from MAN Purworejo during the 2025/2026 academic year, divided equally into an experimental group (33 students) and a control group (33 students). Data were gathered through a post-test writing performance instrument evaluated with a validated rubric and analyzed using the Independent Samples T-Test and Cohen’s d effect size formula. The results indicated a statistically significant difference in creative writing performance between the two groups (p = 0.000 < 0.05). The experimental group achieved a significantly higher mean score (86.00) compared to the control group (75.94). Furthermore, the effect size analysis revealed a Cohen’s d coefficient of 1.48, demonstrating that the implementation of Project-Based Learning has a very large positive effect on students’ ability to write creative satire poetry. In conclusion, PjBL serves as a highly effective and innovative instructional model that enhances both high-order thinking and creative writing competencies in secondary language education.